Immunomodulatory Role of Neuropeptides in the Cornea - Sudan Puri; Brendan M. Kenyon; Pedram Hamrah (Biomedicines, 2022)
The transparency of the cornea along with its dense sensory innervation and resident leukocyte populations make it an ideal tissue to study interactions between the nervous and immune systems. The cornea is the most densely innervated tissue of the body and possesses both immune and vascular privilege, in part due to its unique repertoire of resident immune cells. Corneal nerves produce various neuropeptides that have a wide range of functions on immune cells. As research in this area expands, further insights are made into the role of neuropeptides and their immunomodulatory functions in the healthy and diseased cornea. Much remains to be known regarding the details of neuropeptide signaling and how it contributes to pathophysiology, which is likely due to complex interactions among neuropeptides, receptor isoform-specific signaling events, and the inflammatory microenvironment in disease. However, progress in this area has led to an increase in studies that have begun modulating neuropeptide activity for the treatment of corneal diseases with promising results, necessitating the need for a comprehensive review of the literature. This review focuses on the role of neuropeptides in maintaining the homeostasis of the ocular surface, alterations in disease settings, and the possible therapeutic potential of targeting these systems.